Using modal decompositions to explain the sudden expansion of the mixing layer in the wake of a groyne in a shallow flow. (September 2017) - Higham, J.E.; Brevis, W.; Keylock, C.J.; Safarzadeh, A.
Highlights: The sudden expansion of the mixing layer created in the wake of a single groyne is investigated using Particle Image Velocimetry (PIV). Using low-order representations, created from a Dynamic Mode Decomposition and a search criteria based on a Proper Orthogonal Decomposition, the spatio-temporal mechanism of the sudden expansion is investigated. The present study demonstrates that the sudden expansion is created by the periodic merging of eddies. Abstract: The sudden expansion of the mixing layer created in the wake of a single groyne is investigated using Particle Image Velocimetry (PIV). In the region of the sudden expansion a patch of high Reynolds shear stresses are observed. Using low-order representations, created from a Dynamic Mode Decomposition and a search criteria based on a Proper Orthogonal Decomposition, the spatio-temporal mechanism of the sudden expansion is investigated. The present study demonstrates the sudden expansion is created by the periodic merging of eddies. These eddies originate from the upstream separation and the tip of the groyne and merge with recirculating eddies created, downstream of the groyne, at the interface of the mixing layer and the lateral wall.